ANALYSIS OF THE WASTE MANAGEMENT SYSTEM IN TANA TIDUNG REGENCY - Denny Indrawanto; Muhammad Djaya Bakri; Daud Nawir; Theresia; Fadhilah; Icha Anggriani; Andri Putra Naftali (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Waste management in Tana Tidung Regency faces complex challenges due to population growth, urbanization, and infrastructure limitations. This study aims to analyze the waste management system in Tana Tidung Regency by highlighting the challenges and opportunities in achieving a sustainable environment.waste management infrastructure, such as final disposal sites (TPA) and temporary disposal sites (TPS), is still inadequate. In addition, public awareness of sorting and processing waste is also low. Other constraints include the limited fleet of waste collection vehicles and the minimal use of modern technology. Opportunity aspects such as the development of community-based waste banks, the application of waste processing technologies like biodigesters and waste-to-energy systems, as well as collaboration with the private sector through corporate social responsibility (CSR) programs. The strategy to improve the waste management system, which includes community education, infrastructure investment, and the application of the reduce, reuse, recycle (3R) principle, is deemed important to support the creation of a cleaner and more sustainable environment. waste management in Tana Tidung Regency requires a holistic approach involving the government, the community, and the private sector. By addressing existing challenges and seizing opportunities, Tana Tidung Regency can improve the quality of its waste management towards sustainable development.